Hyper-coagulation and The Used of Anticoagulant for Patient with COVID-19 - Alyssa Claudia V. Gunawan; Bernadette Dian Novita (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Coronavirus SARS-CoV-2 (COVID-19) infection has become a global infection with high mortality and morbidity rate. The pathophysiology of COVID-19 has not yet clear but associated with increasing proinflammatory cytokines and chemokines that leads to cytokine storm. Cytokine storm leads to increasing coagulation that defined by increasing D-dimer, Prothrombin Time (PT), and activated partial thromboplastin time (aPTT). The use of anticoagulant in patient with COVID-19 decrease the mortality rate and become one of the recommended therapy.